2Blood-injection Phobia Inventory (BIPI): Development, reliability and validity - Borda Mas, Mercedes; López Jiménez, Ana Maria; Pérez San Gregorio, Mª Ángeles (Anales de Psicología / Annals of Psychology, 2010)
The aim of this study was to develop the Blood-Injection Phobia Inventory (BIPI) and thus provide a valid and reliable assessment instrument for measuring blood anxiety and blood phobia in Spanish population. This study examined the psychometric properties of the BIPI in 174 Spanish-speaking subjects. The BIPI is a self-administered questionnaire of 18 items or stimulus content and 27 phobic responses that can be used on a 4-point Likert-type format. The scale had a Cronbach’s alpha of .98 and showed good concurrent, convergent, and discriminant validity. Factor analysis of the BIPI identified one significant factor, suggesting that blood phobia is a unitary psychometric construct. This factor explained 76% of stimulus content and 74% of phobic responses of the total variance. Results of this study suggest that the BIPI has adequate psychometric properties that make it a valid and reliable instrument to assess blood phobia in Spanish-speaking individuals.